2014
DOI: 10.1136/bmjopen-2014-005461
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in a marginalised, street-health Australian population: a retrospective cohort study

Abstract: ObjectivesDemographic and presentation profile of patients using an innovative mobile outreach clinic compared with mainstream practice.DesignRetrospective cohort study.SettingPrimary care mobile street health clinic and mainstream practice in Western Australia.Participants2587 street health and 4583 mainstream patients.Main outcome measuresPrevalence and patterns of chronic diseases in anatomical domains across the entire age spectrum of patients and disease severity burden using Cumulative Illness Rating Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 38 publications
0
42
2
Order By: Relevance
“…Portuguese epidemiologic data follows the same tendency, with a high prevalence of multimorbidity (72.7 %) amongst adult patients attending primary care [4]. Factors such as social deprivation [5], marginalisation [6], mental health disorders [5], and poor housing conditions [7] are associated with an increased prevalence of multimorbidity.…”
Section: Introductionmentioning
confidence: 93%
“…Portuguese epidemiologic data follows the same tendency, with a high prevalence of multimorbidity (72.7 %) amongst adult patients attending primary care [4]. Factors such as social deprivation [5], marginalisation [6], mental health disorders [5], and poor housing conditions [7] are associated with an increased prevalence of multimorbidity.…”
Section: Introductionmentioning
confidence: 93%
“…A representative national survey found that nearly half the patients attending general practices in Australia had multiple chronic diseases (47.4%, equating to 32.6% of the general population) 9 . The only assessment of multimorbidity in Indigenous Australians found a higher prevalence of multimorbidity among Aboriginal people attending a Fremantle street health clinic serving a marginalised population than among its non‐Aboriginal patients (50.4% v 44.6%) 10 …”
mentioning
confidence: 99%
“…9 The only assessment of multimorbidity in Indigenous Australians found a higher prevalence of multimorbidity among Aboriginal people attending a Fremantle street health clinic serving a marginalised population than among its non-Aboriginal patients (50.4% v 44.6%). 10 The aims of our study were to compare the prevalence of multimorbidity and its impact on mortality among Aboriginal and non-Aboriginal Australians in New South Wales who had been hospitalised at least once during the previous 10 years. Given the small proportion of Torres Strait Islander people in the NSW hospital data (0.1%), 11 in this article we use the descriptor "Aboriginal" to refer to the original people of NSW and their descendants.…”
mentioning
confidence: 99%
“…[27] This information is critical to appreciate the different demographics of the unselected, undifferentiated populations and presentations seen in primary care compared to the highly selective, well differentiated populations referred to specialists for tertiary level care. The primary care physician requires considerable adaptability and flexibility to meet the health needs of individual patients often with multiple morbidities [28][29][30] and contrasts with the specialist tertiary clinic that deals with the health needs of a group of patients all with same range of diseases or illnesses.…”
Section: Unique Features Of Primary Care Populationsmentioning
confidence: 99%